PARTISIPASI DAN KEHADIRAN MAHASISWA DALAM MENGIKUTI PERKULIAHAN DI MASA NORMAL DAN MASA PANDEMIK COVID 19 - Sudiyono (English Education:Journal of English Teaching and Research, 2021)
This study discusses how the participation and attendance of students following lectures during the normal period and during the Covid 19 pandemic era, even semester of the 2019-2020 academic year. Participants involved were as many as 129 regular class of 2017 students from the English language education study program, the language education faculty of IKIP Siliwangi Bandung. This study used a qualitative research approach, the method of preparing and presenting the research results was made descriptively. The data collection technique was done by observing, interviewing, studying documentation, and searching online. The main instrument is the researcher himself. The results showed that students’ participation and students’ attendance in attending lectures during normal times and during the Covid 19 pandemic era showed a contradiction in circumstances. Keywords: Student participation and attendance, lectures, normal and pandemic covid-19 era.